2015
DOI: 10.4049/jimmunol.1501237
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell–Restricted Insulin/IGF-1 Receptor Deficiency Protects against Skin Inflammation

Abstract: Myeloid cells are key regulators of tissue homeostasis and disease. Alterations in cell-autonomous Insulin/IGF-1 signaling in myeloid cells have recently been implicated in the development of systemic inflammation and insulin-resistant diabetes mellitus type 2 (DM). Impaired wound healing and inflammatory skin diseases are frequent DM-associated skin pathologies, yet the underlying mechanisms are elusive. Here we investigated whether myeloid cell-restricted IR/IGF-1R signalling provides a pathophysiological li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…IGFBP-3 in the IGF independent manner is reported to induce the cellular senescence, 51 and the latter is shown to reduce the viral load. 52 Besides, IGFBP-3 also regulates IGF-1R mediated signaling in macrophages, 53 and the latter immune cell type is involved in regulating the establishment of HSV-1 latency in the trigeminal ganglia. 7,54 Thus, IGFBP-3 in an IGF-dependent or independent manner may participate in regulating viral load in the cornea and trigeminal ganglia of HSV-1 infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-3 in the IGF independent manner is reported to induce the cellular senescence, 51 and the latter is shown to reduce the viral load. 52 Besides, IGFBP-3 also regulates IGF-1R mediated signaling in macrophages, 53 and the latter immune cell type is involved in regulating the establishment of HSV-1 latency in the trigeminal ganglia. 7,54 Thus, IGFBP-3 in an IGF-dependent or independent manner may participate in regulating viral load in the cornea and trigeminal ganglia of HSV-1 infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to communicating anti-inflammatory signals directly to epithelial cells, macrophages also regulate communication in the epidermis. Knuever and colleagues have shown that myeloid cell-restricted insulin and IGF-1 receptor deficiency protects mice from skin inflammation by decreasing pro-inflammatory cytokine production from epidermal cells (Knuever et al, 2015). Monocyte and macrophage-derived IGF-1 has also been identified as a critical factor in skeletal muscle repair (Tonkin et al, 2015).…”
Section: Protective Roles For Anti-inflammatory and Anti-fibrotic Macmentioning
confidence: 99%
“…Resident macrophages obtain M1 or M2 phenotypes, depending on the microenvironment and the stimuli present, such as this of insulin that induces AKT kinase signals (3, 41). In the context of insulin resistance, peripheral macrophages acquire an anti-inflammatory M2-like phenotype, characterized by increased expression of M2 markers and reduced secretion of pro-inflammatory factors upon stimulation (3, 42). In addition, insulin resistant macrophages produce reduced levels of NO upon TLR stimulation in vivo and in culture and exhibit reduced bactericidal capacity in vivo (3).…”
Section: Introductionmentioning
confidence: 99%